CONSUMPTION BEHAVIOR OF MODERN MUSLIM SOCIETIES VIEWED FROM THE PERSPECTIVE OF ISLAMIC ECONOMICS - Hidayati, Amalia Nuril (Yayasan Education and Social Center, 2024)
Most people in the world now live in the modern era, where modernization has had a positive impact in making activities easier. This phenomenon is closely related to consumer behavior that is accepted by society. The aim of this research is to explore modern Muslim consumption behavior from an Islamic Economics perspective. The method used in this research is descriptive qualitative, namely reviewing various literature references according to the research topic. The research results show that in an Islamic economic perspective, consumption must consider spiritual and moral aspects, not only fulfilling worldly needs but also getting closer to Allah and preparing for the afterlife. Consumption must avoid waste, extreme attitudes, and must be in accordance with Islamic principles. Islamic consumption behavior ethics need to be considered by emphasizing the selection of halal goods and services, avoidance of haram ones, and wise management of resources for spiritual and social benefits. In the modern era, there is a challenge to Islamic consumption behavior, namely applying Islamic principles in the global financial system, while the opportunity lies in increasing awareness about Islamic values in sustainable consumption. Muslim consumers need to maintain consistency in paying zakat, infaq and alms, and ensure that their consumption behavior is fair and in accordance with Islamic principles to achieve sustainable social and economic prosperity, especially amidst global economic changes. Thus, the principles of modern Islamic consumption behavior when viewed from Islamic economics will be implemented consistently, leading to harmonious and sustainable prosperity both in this world and the hereafter